Dry Eye Indexes Estimated by Keratograph 5M of Systemic Lupus Erythematosus Patients without Secondary Sjögren's Syndrome Correlate with Lupus Activity. (29th August 2019) - Wang, An; Gu, Zhengyu; Liao, Rongfeng; Shuai, Zongwen
Abstract : Purpose . To investigate the incidence, severity, and influencing factors of dry eye in systemic lupus erythematosus (SLE) patients without secondary Sjögren's syndrome (sSS). Methods . A total of 78 patients who were diagnosed with systemic lupus erythematosus and met inclusion criteria were selected as the study subjects in this cross-sectional study. Tear meniscus height (TMH) and noninvasive Keratograph tear breakup time (NIKBUT) including NIKBUT-first and NIKBUT-average of the subjects were measured using a noninvasive ocular analyzer, the Keratograph 5M (Oculus, Wetzlar, Germany). Symptoms related to dry eye were assessed using the Ocular Surface Disease Index (OSDI). The severity of SLE was evaluated by Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K). Results of the levels of 4 serum antibodies were collected from the patients' medical records. Correlations between SLEDAI and various ocular surface parameters were analyzed, and multiple-factor binary logistic regression analysis was conducted. Results . In the study subjects, mean TMH was 0.22 mm, mean NIKBUT-first was 9.12 s, and mean OSDI was 13.14. The subjects (19 eyes) whose NIKBUT-average was < 10 s and OSDI was ≥ 13 accounted for 24.36% of all the included patients. SLEDAI showed a statistically significant correlation with TMH ( r  = −0.233, p = 0.040 ), NIKBUT-first ( r  = −0.254, p = 0.025 ), NIKBUT-average ( r  = −0.343, p = 0.002 ), and OSDI ( r  = 0.256, p = 0.024 ). According to multiple-factor binary logistic regression analysis, SLEDAI could be considered as a risk factor of the incidence of dry eye in SLE patients without sSS. Conclusions . One-fourth of the SLE patients without sSS suffered from dry eye, and the severity of dry eye correlated with the activity of SLE.